An ontology-based approach for developing data exchange requirements and model views of building information modeling. Issue 3 (August 2016) - Lee, Yong-Cheol; Eastman, Charles M.; Solihin, Wawan
Abstract: Each domain industry requires the detailed specifications for sharing and exchanging building information models throughout the design, construction, and operation phases. Industry Foundation Classes (IFC) Model View Definitions (MVDs) specify required information for exchanges of building model data among building project experts. The data involves the identification of model semantics shared by two or more applications. However, since no robust standard for defining building semantics and requirements for data exchange has been agreed upon, information embedded in domain-specific MVDs are generated separately and are vague in scope, which results in a lack of consistency. In addition, the Information Delivery Manual (IDM) that includes exchange specifications needed for each exchange process of a product model is manually defined in a paper-based document. Because there is no clear logical link between the units of information in the exchange requirements of an IDM, and those of MVDs, the mapping that translates requirements of an IDM into ones of an MVD is open to various interpretation, without semantic and logical consistency. Such challenges might result in redundant requirements and rules for data exchange that are not supposed to be handled in the process of MVDs. To ameliorate this situation, this research proposes the new approach of formalizing domain knowledge and defining accurate data modules for model views. To achieve this goal, the authors employed ontological principles for generating an IDM for the precast concrete domain and for linking its MVD with formal information models. The formalized structure of domain knowledge is expected to support defining explicit data modules and developing manageable relationships among entities using semantic reasoning so that domain professionals and software vendors can identify the intents of the requirements of mapped MVDs and keep track of mapping problems. Moreover, to integrate IDM and MVD development processes, the ontology-based IDM is parsed and translated from OWL/XML to mvdXML, which automatically generates MVD documentation in the IfcDoc tool.